Efficiency and productivity change in Central Bank of Malaysia: Evidence from stochastic frontiers and brownian motion - Baten, Md Azizul; Kassim, M. M.; Ramli, Razamin (CESER Publications, 2015)
This study evaluated the efficiency of Central Bank of Malaysia and forecasted the productivity change with Brownian motion using both the output oriented Data Envelopment Analysis (DEA) and Malmquist DEA methods.It considered Net Profit and Loan and Advances as outputs and Deposit, Reserve and Fund from International Monetary Fund as inputs of the Central Bank of Malaysia over the time period from 2000 to 2012. The minimum efficiency (0.77) was observed for net profit and Loan and Advances of the central Bank of Malaysia in the year 2004.During the time period, the mean efficiency of the central Bank of Malaysia was found to be 0.926. The result showed that productivity change of output variables was decreased for the Central Bank of Malaysia in most of the years.The increasing productivity change was recorded in the years of 2000, 2001, 2009 and 2010. Gold and Foreign exchange were found to be positive and have significant impact on productivity of Central Bank of Malaysia. Finally, the productivity change of Central Bank of Malaysia was forecasted using Brownian motion and observed increasing over time.